Leadership, Culture, and Motivation Impact on Employee Performance: A Quantitative Analysis: Dampak Kepemimpinan, Budaya, dan Motivasi Terhadap Kinerja Karyawan: Analisis Kuantitatif - Dafa Fadelarti Suherman; Hasan Ubaidillah (Universitas Muhammadiyah Sidoarjo, 2024)
This quantitative study investigates the influence of leadership style, organizational culture, and motivation on employee performance. Employing an accidental sampling technique, 85 respondents from various backgrounds were surveyed through distributed questionnaires. Utilizing multiple linear regression analysis via SPSS 22, the findings reveal that leadership style, organizational culture, and motivation significantly affect employee performance. These results hold implications for organizational management and human resource practices, emphasizing the importance of fostering effective leadership, nurturing a positive organizational culture, and enhancing employee motivation to optimize overall employee performance.Highlights : The study examines the impact of leadership style, organizational culture, and motivation on employee performance through quantitative analysis. Accidental sampling involving 85 respondents was employed, emphasizing diverse backgrounds for comprehensive insights. Results underscore the significant influence of leadership style, organizational culture, and motivation on employee performance, with implications for effective management and human resource strategies. Keywords: Leadership Style, Organizational Culture, Motivation, Employee Performance, Quantitative Analysis